Clinical Features and Predictors of Lethal Outcome in Tick-Borne Encephalitis: A Retrospective Study from Lithuania - G. Rynkevič; E. Žilinskas; D. Streckytė; D. Radzišauskienė; R. Mameniškienė (Neurologijos seminarai)
Background. In Lithuania, the incidence rate of tick-borne encephalitis (TBE) increases and remains the highest in the whole Europe. Diverse clinical manifestations cause difficulties in diagnosing and treating this infectious disease. The aim of the study was to analyze clinical manifestations of the TBE and to indicate predictive variables for unfavorable outcome.